2002
DOI: 10.1093/alcalc/37.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention for Problem Drinkers: Readiness to Participate Among General Practitioners and Nurses in Swedish Primary Health Care

Abstract: An exploration was made of attitudes and practices of general practitioners (GPs) and nurses concerning early identification of, and intervention for, alcohol-related problems. Sixty-five GPs and 141 nurses in 19 primary health centres in a county in southern Sweden answered a 28-item questionnaire before implementation of an intervention programme. The questionnaire covered experiences with patients with alcohol-related health problems, knowledge and perceived capacity concerning early identification and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 31 publications
6
74
0
14
Order By: Relevance
“…However, most health care systems focus on the management of acute illness and chronic health conditions. Health care providers face substantial barriers to providing preventive services aimed at achieving health-related behaviour change, as they often lack the time, knowledge, and skills [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, most health care systems focus on the management of acute illness and chronic health conditions. Health care providers face substantial barriers to providing preventive services aimed at achieving health-related behaviour change, as they often lack the time, knowledge, and skills [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the knowledge and attitudes of nurses toward alcohol and alcoholism have indicated that nurses believe that their interventions have little influence on the drinking habits of their patients [10] , that nurses feel less confidence than other health professionals when using their knowledge and skills to treat alcoholic patients [11] and that after training programs and courses on the area, they showed positive changes in their skills and knowledge of alcohol and associated problems [12] . With regard to attitudes, study results [12] have suggested that nursing professionals have moral opinions and attitudes toward alcohol and associated problems despite considering alcoholism a disease [2] , judging patients' treatment motivation as recovery [12] and disagreeing that alcoholics have character flaws [3,13] .…”
mentioning
confidence: 99%
“…As documented in other studies, the reasons why the delivery of brief alcohol interventions may be suboptimal include lack of time, lack of workplace support, poor financial reimbursement and feelings of inadequacy by healthcare staff (37,(40)(41)(42); and we believe these factors also apply in the UK. To combat some of these shortfalls, it may be important to continuously educate healthcare professionals, who are committed to addiction reduction, on the public health damage of risky drinking and the effectiveness of brief alcohol interventions (43)(44)(45).…”
Section: Discussionmentioning
confidence: 53%